The challenges of school reform : implementation, impact, and sustainability - Solmon, Lewis C.; Agam, Kimberly Firetag; Priagula, Citadelle (Emerald Publishing Limited : IAP-Information Age Publishing Inc., 2006)
This work expands on the ideas and themes discussed in the first two volumes in this series on education policy: The first book -- Talented Teachers: The Essential Force for Improving Student Achievement -- examines the importance of teacher quality. Years of research have repeatedly confirmed what we inferred to be true--outside of the home environment, the quality of a student's teacher has the strongest impact on learning. After talented teachers were found to be a powerful component for bettering education, the second book -- Improving Student Achievement: Reforms that Work -- introduces reform ideas and programs that positively impact both teacher quality and student work. Now, The Challenges of School Reform: Implementation, Impact, and Sustainability deepens these discussions by exploring the answers to questions regarding ensuring the longevity and sustained success of effective school reform.
"A compilation of the proceedings from the 2005 Milken Family Foundation National Education Conference (NEC) held in Washington, D.C. in April 2005"--P. xiv.
Keywords: School improvement programs -- United States -- Congresses.; Educational change -- United States -- Congresses.; Educational planning -- United States -- Congresses.; Education -- Educational Policy & Reform -- General.; Educational systems and structures.; Educational strategies and policy.; elektronické knihy; electronic books